Transient abnormal myelopoiesis of a newborn not associated with chromosome 21 abnormalities or GATA1 mutations. Issue 2 (30th August 2014) - Nakashima, Megan O.; Shetty, Shashirekha; Chicka, Michael; Flagg, Aron; Eng, Charis; Cotta, Claudiu V.
Abstract Transient abnormal myelopoiesis (TAM) is a disorder of Down syndrome newborns characterized by megakaryocytic blasts indistinguishable from acute myeloid leukemia (AML), which undergoes spontaneous remission. Acquired GATA1 mutations are present in blasts of both TAM and the subsequent AML which sometimes develops. We present a unique case of a newborn with leukemic megakaryoblasts indistinguishable from those of TAM who had neither extra material from chromosome 21 in the germline or blasts, nor evidence of GATA1 mutations. These findings suggest there are other genetic abnormalities that can lead to TAM besides GATA1 mutation in the setting of trisomy 21. Pediatr Blood Cancer 2015;62:353–355. © 2014 Wiley Periodicals, Inc.